IMPLIKATUR PERCAKAPAN SISWA TUNAGRAHITA DAN GURU DI SEKOLAH LUAR BIASA - Lega hidayati; Wiryotinoyo, Mujiyono; Kuntarto, Eko (Universitas Wiralodra, 2022)
ABSTRAK Children with special needs are children who have obstacles and limitations from various aspects including in terms of language skills. In mentally retarded children, language skills are not achieved perfectly and the speed in language is also slow compared to other normal children, this is influenced by the intellectual function of a person who is below the average normal person. So that in communicating, teachers and students with mental retardation have differences compared to students in other public schools. This can be seen during the learning process, the teacher explains the teaching material, but the students catch it with different intentions and vice versa. Therefore, teachers need more knowledge and understanding of the language they use so that the meaning of their speech can be conveyed, especially in conversational implicatures. So this can be seen in the lingual form and form of a pragmatic unit description on the conversational implicatures of teachers and students with mental retardation. This research is qualitative with the method of listening and the research instrument is the researcher himself. Thus the research data found in the lingual form and form of pragmatic units on the conversational implicatures of mentally retarded students and teachers in special schools. KEYWORDS: Pragmatics; Implicature; mentally retarded students. ABSTRAK Anak berkebutuhan khusus merupakan anak yang memiliki kendala dan keterbatasan dari berbagai aspek diantaranya dari segi kemampuan berbahasa. Pada anak tunagrahita kemampuan berbahasa tidak tercapai dengan sempurna dan kecepatan dalam berbahasa juga lambat dibandingkan dengan anak normal lainnya, hal ini dipengaruhi oleh fungsi intelektual yang berada dibawah rata-rata orang normal, Sehingga dalam berkomunikasi Guru dan Siswa tunagrahita memiliki perbedaan dibadingkan dengan siswa di sekolah umum lainnya. Hal ini dapat dilihat saat proses pembelajaran guru memaparkan materi ajar namun siswa menangkap dengan maksud berbeda-beda begitupun sebaliknya. Oleh sebab itu, guru memerlukan pengetahuan dan pemahaman yang lebih terhadap bahasa yang digunakannya agar maksud tuturannya dapat tersampaikan terutama dalam implikatur percakapan. Sehingga hal ini dapat dilihat dalam bentuk deskripsi bentuk lingual dan satuan pragmatis pada implikatur percakapan Guru dan Siswa tunagrahita. Pada penelitian ini bersifat kualitatif dengan metode simak dan instrumen penelitian merupakan peneliti sendiri. Dengan demikian ditemukan data penelitian yang berupa bentuk lingual dan satuan pragmatis pada implikatur percakapan Siswa tunagrahita dan Guru di SLB. KATA KUNCI : Pragmatik, Implikatur, Siswa Tunagrahita.